Nationalism and socialism portrayed in the Novels of the Indo-Anglian Novelist trio : Raja Rao, Mulk Raj Anand and R.K Narayan - Hossain, Mehruna (BRAC University, 2014)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2013.